REFORMULASI HUKUM PERKAWINAN ISLAM RESPONSIF GENDER - Maisyal, Nurul (MUWAZAH, 2016)
This paper are the result of research that aims to find about formulation of the Marriage Law of Islam in Indonesia that are gender responsive. This normative juridical research method with the approach of legislation, conceptual and historical. Analysis of legal materials using prescriptive analysis, by interpretation, argumentation and legal logic. The results showed that, gender relations in Islam Marriage Law in Indonesia, as stipulated in Law No. 1 of 1974 on Marriage and the Compilation of Islamic Law, was still gender bias. This is evidenced by still many chapters to be scrutinized, particularly Article 31 paragraph (3) and Article 34, concerning husband-wife relationship patterns unequal gender. Therefore, the need for a reformulation of Islamic Marriage Law to make it more gender responsive. Legal issues are problematic in Marriage Law of Islam, namely concerning the minimum age of marriage, the marriage guardian, polygamy and nushuz also need reformulated, based on three basic values of law as an analysis, by considering the concepts of Islamic law, in order to study on the legal that are gender responsive acceptable by the people.Paper ini merupakan hasil penelitian yang bertujuan untuk menemukan tentang formulasi mengenai Hukum Perkawinan Islam di Indonesia yang responsif gender. Penelitian yuridis normatif ini menggunakan pendekatan perundang-undangan, konseptual dan historis. Analisis bahan hukum menggunakan preskriptif analisis, dengan penafsiran, argumentasi dan logika hukum. Hasil penelitian menunjukan bahwa, relasi gender dalam hukum perkawinan Islam di Indonesia, yang tertuang dalam Undang-Undang RI Nomor 1 Tahun 1974 tentang Perkawinan dan Kompilasi Hukum Islam, masih bias gender. Hal ini dibuktikan dengan masih banyaknya pasal-pasal yang perlu dikritisi, khususnya Pasal 31 ayat (3) dan pasal 34, mengenai pola relasi suami-isteri yang tidak setara gender. Oleh karena itu, perlu adanya reformulasi Hukum Perkawinan Islam agar lebih responsif gender. Isu hukum problematis dalam Hukum Perkawinan Islam, yaitu tentang batas usia menikah, wali nikah, poligami dan nusyūz juga harus direformulasi, berbais tiga nilai dasar hukum sebagai analisa, dengan mempertimbangkan konsep-konsep hukum Islam, agar kajian tentang hukum yang responsif gender,diterima oleh masyarakat.